Bovine stem cell factor: Production of a biologically active protein and mRNA analysis in cattle infected with Trypanosoma congolense - Mertens, B.; Muriuki, C.; Muiya, P.; Andrianarivo, A.; Mwangi, S.; Logan-Henfrey, L.L. (Elsevier, 1997)
The cDNA coding for the soluble form of bovine stem cell factor (boSCF-Ala-105) was cloned and recombinant protein was produced in bacteria as a histidine tagged-protein. The protein was purified from the inclusion bodies in one step by metal chelation chromatography under denaturing conditions. Recombinant bovine SCF was shown to act synergistically with interleukin 3 (IL-3) and erythropoietin (EPO) in stimulating the growth of bone marrow progenitor cells such as colony forming units-granulocyte macrophage (CFU-GM) and burst forming units-erythroid (BFU-E). Analysis of SCF mRNA expression by reverse transcription-polymerase chain reaction (RT-PCR) revealed that the transcripts were detectable in bone marrow, lymph node and spleen of cattle, and that the level of transcription was upregulated in lymph nodes of cattle infected with Trypanosoma congolense. Two isoforms of SCF mRNA were amplified by RT-PCR. The availability of recombinant bovine SCF provides a valuable tool for studying the role of SCF in the development, growth and differentiation of bovine hematopoietic cells.